Breast Milk Lipidome Is Associated With Maternal Diet and Infants' Growth - Calvo-Lerma, Joaquim; Selma-Royo, Marta; Hervas, David; Yang, Baoru; Intonen, Linda; González, Sonia; Martínez-Costa, Cecilia; Linderborg, Kaisa M.; Collado, Maria Carmen (Frontiers in Nutrition, 2022)
Objectives The fatty acid (FA) composition of breast milk is a relevant aspect related to the development of the lactating infant. The present study aimed at exploring correlations between dietary intake of macro- and micronutrients with the FA profile in breast milk, and the possible implication for infants' growth. Study Design Breast milk samples from a cohort of lactating women were collected 7–15 days postpartum. The FA profiles in triacylglycerol (TAG) and phospholipid (PL)-rich fractions were analyzed by gas chromatography. Diet was registered during the third trimester of pregnancy by means of a food frequency questionnaire (FFQ). In addition, anthropometric measurements of infants were collected from gestation and up to 12 months postpartum. Results The FA profile in breast milk was characterized by a median of 37.4, 41.3 and 16.8% of saturated, monounsaturated, and polyunsaturated FAs, respectively. From the dietary components, zinc, iron, and B group vitamins were correlated positively with the proportion of total n-3 FAs in TAG and C20:5 n-3 in PL. Lycopene, vitamin E, zinc, and vitamin B2 showed a similar correlation with total polyunsaturated fatty acid (PUFA), total n-6 FAs, C20:4 n-6, and C18:2 n-6 in TAG. Regarding food groups, nuts showed the strongest association with several PUFA both in TAG and PL, while the vegetable group was also positively associated with C18:3 n-3. Furthermore, the concentration of linolenic acid (C18:3 n-3) and palmitic acid (C16:0) were positively associated with increased length for age (LFA) and weight for age (WFA) at 12 months compared with birth [ΔLFA −0.16 (−0.85, 0.37); ΔWFA −0.26 (−0.77, 0.21)]. Conclusions Mothers' intake of nuts, dietary sources of zinc, iron, and B group vitamins were identified as potential predictors of a high-unsaturated FA profile in breast milk. In addition, linolenic and palmitic acids in breast milk were positively associated with infants' growth in the first year of life.